2017 IEEE Conference on Communications and Network Security (CNS) 2017
DOI: 10.1109/cns.2017.8228657
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental limits of covert communication over MIMO AWGN channel

Abstract: Fundamental limits of covert communication have been studied for different models of scalar channels. It was shown that, over n independent channel uses, O( √ n) bits can be transmitted reliably over a public channel while achieving an arbitrarily low probability of detection (LPD) by other stations. This result is well known as the square-root law and even to achieve this diminishing rate of covert communication, all existing studies utilized some form of secret shared between the transmitter and the receiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 15 publications
2
45
0
Order By: Relevance
“…This leads to the fact that the probability that the spread-spectrum techniques fail to hide wireless transmissions is unknown, significantly limiting its application. The fundamental limit of covert communication has been studied under various channel conditions, such as additive white Gaussian noise (AWGN) channels [17], binary symmetric channels [18], discrete memoryless channels [19], and multiple input multiple output (MIMO) AWGN channels [20]. It is proved that O( √ n) bits of information can be transmitted to a legitimate receiver reliably and covertly in n channel uses as n → ∞.…”
Section: A Background and Related Workmentioning
confidence: 99%
“…This leads to the fact that the probability that the spread-spectrum techniques fail to hide wireless transmissions is unknown, significantly limiting its application. The fundamental limit of covert communication has been studied under various channel conditions, such as additive white Gaussian noise (AWGN) channels [17], binary symmetric channels [18], discrete memoryless channels [19], and multiple input multiple output (MIMO) AWGN channels [20]. It is proved that O( √ n) bits of information can be transmitted to a legitimate receiver reliably and covertly in n channel uses as n → ∞.…”
Section: A Background and Related Workmentioning
confidence: 99%
“…where (13) is because of the union bound and the mutual independence of the cells; (14) is from (6). The last term goes to 1 as n tends to infinity.…”
Section: B Detoured Mh Schemementioning
confidence: 99%
“…Such scenarios arise in underwater acoustic communication [1] and dynamic spectrum access in wireless channels, where secondary users attempt to communicate without being detected by primary users or users wish to avoid the attention of regulatory entities [2]. The information theory for the low probability detection communication was first characterized on AWGN channels in This [3] and DMCs in [2] [4], and later in [5] and [6] on BSC and MIMO AWGN channels, respectively. It has been shown that LPD communication follows the following square root law.…”
Section: Introductionmentioning
confidence: 99%